ATTENTIONAL DISTRACTION IN APP-BASED LANGUAGE LEARNING WITH MOBILE PHONES: A LITERATURE REVIEW - Rosyidah, Risvi Uly; Hamim, Hamim; Cholili, Abd Hamid (J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research reviews attentional distraction factors in mobile phone-based language learning and proposes the Interactive Model of Attentional Distraction Management in learning as a new theoretical framework. Distractions from multitasking, notifications and social media apps were shown to reduce attention as well as memory function, hindering important cognitive processes in language acquisition. Individual factors such as age, gender and experience also affect the ability to manage distractions, which reinforces the urgency of adaptive attentional management. This new theoretical framework offers an interactive and personalised solution with three main components: cognitive, psychological and social environmental elements. Mobile phone-based applications can adjust learning settings in real-time, providing better user control over distractions. This model is expected to improve learners' focus, maintain attention, and support the effectiveness of technology-based language learning.